Implementasi metode pembelajaran demonstrasi dengan bahasa tubuh pada mata pelajaran Pendidikan Agama Islam dan Budi Pekerti di SMPLB B Yakut Purwokerto - Khanifah, Nurkhasna; Umar Fakhruddin, Asef (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2025)
The demonstration learning method is a teaching method that uses instruction with the aim of providing a more detailed explanation of the material being taught, in order to show children how to carry out a specific action. In the application of the demonstration learning method, either the teacher or the students demonstrate a particular technique or action to their peers. The purpose of this observation is to understand the implementation of the demonstration learning method using body language in Islamic Religious Education and Character Education subjects. This research was conducted at SMPLB B Yakut Purwokerto, because the school applies the demonstration method in teaching Islamic Religious Education, and uses body language to facilitate understanding for students with hearing impairments. Therefore, this study analyzes how the demonstration learning method using body language is implemented in the Islamic Religious Education and Character Education subject. This research uses a qualitative approach, in which the researcher directly observes the learning process at SMPLB B Yakut Purwokerto. The methods used in this study include interviews, observation, and documentation. The researcher used data analysis techniques involving data reduction, data presentation, as well as drawing conclusions and verification, followed by data validity testing. The results of this research indicate that the planning of the demonstration method using body language in Islamic Religious Education and Character Education at SMPLB B Yakut Purwokerto has been well executed, supported by the teacher's success in providing guidance and instruction. This is also reinforced by the presence of teaching modules prepared by the teacher. The module includes time allocation, learning objectives, learning outcomes, instructional materials, facilities and infrastructure, learning activities, and assessment.